Peta Tematik Kesesuaian Paramater Fisika Air Untuk Budidaya Rumput Laut (Eucheuma cottoni) - Abdul Muqsith; Abdul Wafi; Heri Ariadi (Samakia : Jurnal Ilmu Perikanan, 2022)
Seaweed is a commodity that widely cultivated in coastal waters. The purpose of this study was to map the level of water physics parameters suitability for seaweed (Eucheuma cottoni) cultivation activities in Banyuputih District, Situbondo Regency. This research was conducted in January-March 2019 with the concept of field research and spatial analysis of the parameter data included the temperature, salinity, current, brightness, and water depth which were then analyzed using the Inverse Distance Weighting (IDW) method and overlay on the GIS (Geographic Information System) application to create a visualization model for thematic land suitability maps. The results showed that all physical parameters were still suitable for seaweed cultivation activities. Temperature and salinity parameters fluctuated dynamically with temperature values ​​of 27.2±1.3-28.0±1.5 and salinity 29.0±0.7-30.1±0.6. Meanwhile, the current parameters, brightness, and depth of the waters fluctuated steadily with values ​​for current parameters 17.2±1.1-37.0±2.2, brightness 4.9±0.5-6.6±0.2, and depth 6.8±0.3-10.9±0.2. All water parameters were described in the thematic map display for land suitability based on geographic information system data. So as for the conclusions of this study, based on the condition of the physical parameters of the water (salinity, temperature, current, brightness, and depth), the condition of the waters in the coastal area of ​​Banyuputih District was very feasible to be used as a place for seaweed (Eucheuma cottoni) cultivation which was depicted through the description of the thematic map figure.